Большие уклонения для обратных стохастических уравнений с квадратичным ростом - Качанова, И.А. (Доповіді НАН України, 2011)
Доведено принцип великих відхилень для обернених стохастичних рівнянь, пов'язаних із сім'єю марковських процесів з малою дифузією, коефіцієнти яких залежать від малого параметра. При обгрунтуванні даного принципу встановлено рівномірну на компактах збіжність розв'язків напівлінійних параболічних рівнянь другого порядку з малим параметром при старшій похідній і коефіцієнтами, що залежать від цього параметра і слабко збігаються в L2,loc. We prove the large deviation principle for backward stochastic equations related to a family of Markov processes with small diffusion, where the coefficients of these forward-backward equations depend on a small parameter. To prove this principle, we show the convergence of solutions of second-order semilinear parabolic partial equations, which is uniform on compact sets, with small parameter by the second derivative and coefficients which depend on this parameter and weakly converge in L2,loc.